THE ENERGY SECTOR OF UZBEKISTAN: PRESENT STATE AND PROBLEMS - KENISARIN, Murat (CENTRAL ASIA AND THE CAUCASUS, 2004)
In this century Uzbekistan’s socioeconomic development will be determined by the degree of efficiency with which it will exploit its fuel re-serves. This calls for an all-round investigation of the energy generation and consumption in all spheres of national economy as well as for monitoring energy consumption level and the long-term dynamics created by the state’s tax and price policy. A careful analysis of power consumption in individual branches of our country and in the developed countries should prompt ways and means of lowering this index in the economy of Uzbekistan. Table 1 presents the key indicators of the world and Uzbekistani power production. The re-public exceeds by 23% the average world level where per capita power consumption is concerned and is below by 20% in per capita electric-power consumption which means that Uzbekistan is close to the average world level. These resources, how-ever, are used inefficiently: the national economy’s power consumption is 9 times higher than the world’s average level while electricity intensity per GDP unit is 6 times higher. A gap between Uz-bekistan and the developed countries is much wid-er: 2,228 and 1,114 times, respectively. This dis-crepancy is caused by the artificially lower fuel prices that existed in the Soviet Union and were inherited by many of the CIS countries that had never required, and is not requiring, energy-saving measures. In the West the energy crisis of 1973-1974 speeded technological progress in the energy-saving sphere; Austria, Denmark, Germany, Nor-way, Sweden, Switzerland, and Japan acquired the best results in energy saving mainly because all of them with the exception of Norway, are fuel import-ers. The developed legal basis, reliable and vast statistics, the ramified system of norms and stand-ards as well as integrated and systemic research were behind their achievements in the energy-sav-ing sphere. This shows that no sustainable national eco-nomic development in Uzbekistan is possible with-out structural changes in the economic sphere and a complex of measures designed to considerably reduce power consumption.